When rights embrace responsibilities : biocultural rights and the conservation of environment - Sajeva, Giulia, 1986- (New Delhi : Oxford University Press, 2019)
This title critically assesses the foundations, content and implications of biocultural rights and develops new perspectives and ideas concerning their potential applicability for promoting the socio-economic interests of indigenous people and local communities. It further explores the controversial relationship of interdependence and conflict between conservation of environment and protection of human rights.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 17, 2019).
Keywords: Biodiversity conservation -- Law and legislation; Indigenous peoples -- Ecology; Environmental protection